The Implications of Applying Metacognitive Strategies on English Writing Skills of Students: A Perspective on Problem Solving and Students’ Self-Efficacy - Mustain Mustain; R A Khaeru Ahmadi (Technium Social Sciences Journal, 2023)
This research aims to examine the implications of metacognitive strategies on problem-solving and students’ self-efficacy in English writing skills. The study utilized a Quasi-Experimental research design involving a sample size of 100 participants. Tests were used to assess writing skills, and questionnaires were employed to gather data on the application of these strategies from the perspectives of problem-solving and self-efficacy. Subsequently, both the experimental and control groups received their respective treatments. The data was then analyzed using Analysis of Covariance (ANCOVA) with the assistance of SPSS 22. The research findings indicated that students who were exposed to the metacognitive strategy showed significant improvements in problem-solving and self-efficacy. This study contributes new insights into the importance of metacognitive strategies in the field of education.